Branding Problems of Jaffna Made Products: A Multiple Case Studies of Manufacturers in Jaffna District. - Malathy, R.K.M.; Shivany, S. (Research gate, 2018)
Branding is a key tool in marketing to any business whether local products or foreign products to win the market. good branding boosts the business activities and gains competitive advantages in the market place. This study shows the branding problems of Jaffna made products, and why they are ineffective in the market place. In the post war Jaffna Market there are number of new business from other districts of Sri Lanka, as well as from foreign countries have penetrated into the market. Due to that, consumers have more bargaining power than manufacturers, the have more choices to purchase product, because many branded products are available in the market place. Jaffna manufacturers transformed their businesses activities due to prolonged war and recently returned to their livelihood businesses. Due to the poor knowledge they have on branding, they face stiff competition in market place. This study analyzed the reasons behind the unsuccessfulness of Jaffna made products. Through the qualitative research methodology ten multiple case studies from 10 Jaffna Manufacturers were selected to collect data. Collected data were analyzed using content analysis method to identify the branding problems of Jaffna made products. This study has found that there are many reasons behind the branding problems, such as Poor-quality packaging, inadequate supporters to develop, lack of knowledge on branding, good external brands from other places, Poor quality production, Poor technology adoption, non-attractive packaging, insufficient marketing opportunity, and Deprived branding promotion. Each brand has unique problems in their labels and features. Each brand is compared with good quality brands and the ideas for improvement have been suggested by the researchers. This study found that due to many reasons they could not achieve the target market even though the Jaffna manufacturers have good product, Jaffna Manufacturers have to work hard to improve their brands to match the quality standards.
Keywords: Branding problems; External branding and Strategy; Multiple Case studies; Manufacturers